Anthriscus nemorosa essential oil exhibits anxiolytic and antidepressant like effects and improves memory on amnesia induced rats - Akbaba, Emel Aydın; Bağcı, Eyüp; Hritcu, Lucian (My University, 2015)
Anthriscus (commonly known as beaked chervil, beaked parsley, rough chervil) is one of the aromatic members of the family Apiaceae used for medicinal purposes in traditional medicine around the world including Turkey. The members of this genus have been consumed as food and/or drink. Antitussive, antipyretic, analgesic, diuretic and memory improving effects are well documented in folk medicine. In the present study, the effects of inhaled A. nemorosa essential oil on spatial memory performance, anxiety and depression were assessed in scopolamine-treated rats. Decrease of spontaneous alternations percentage within the Y-maze task, increase of working memory errors and reference memory errors within the radial arm maze task, increased swimming time within the forced swimming test and decreased time spent in the open arm percentage within the elevated plus maze task were exhibited on scopolamine-induced rats. Exposure to A. nemorosa essential oil significantly improved these parameters, suggesting positive effects on spatial memory formation, anxiety and depression.. Therefore, our results suggest that exposure to A. nemorosa essential oil ameliorates scopolamine-induced spatial memory impairment, anxiety and depression.
Bildiri - Yayımlanmış
Keywords: Anxiety; Depression; Anthriscus nemorosa essential oil; Spatial memory; Alzheimer’s disease